The language of mental pain: feel like, feel as if - Catherine Paulin (Lexis: Journal in English Lexicology)
In this article, I am interested in the relationship between the experience of mental pain, the sensations and emotions it engenders and its verbal representations in autobiographical writings. I have attempted to provide an account of the verbalization of mental pain by analyzing the constructions feel like + NP, feel like / as if + propositional content. These constructions enable the subject to represent his or her experience in terms of an irreal experience and, by mobilizing a comparison, to highlight an important aspect of mental pain.